Pembuatan Komposter Saniter Sebagai Alternatif Pegolahan Sampah Organik Di Kelurahan Karang Besuki Di Kota Malang - Mufidatul` Islamiyah; Tri Wahyuni; Fadilla Cahyaningtyas; Justita Dura (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
The increasing volume of organic waste in urban areas, such as Karang Besuki Village in Malang City, requires effective solutions to manage this waste sustainably. Currently, organic waste in the Karang Besuki sub-district, Malang City is still being collected at the Kali Urang Karang Besuki landfill, so this service aims to evaluate the creation of a sanitary composter as an alternative for processing organic waste. Sanitary composting, as a waste processing technology that integrates the principles of sanitation and composting, offers great potential for reducing the burden of organic waste and producing high-quality compost. This study includes the design and implementation of sanitary composters in several locations in Karang Besuki Village, as well as an analysis of their effectiveness in processing organic waste and their impact on environmental cleanliness. The research results show that the use of a sanitary composter not only reduces the volume of organic waste significantly but also improves soil quality through compost production. Implementation of this technology could become a sustainable model for organic waste management in other urban areas, reducing dependence on landfill and supporting broader environmental initiatives.